1996
DOI: 10.1113/jphysiol.1996.sp021405
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of initial doublets in the discharges of motoneurones of two different inspiratory muscles in the cat.

Abstract: 1. Trains of action potentials in motoneurones frequently commence with an initial doublet;i.e. a uniquely short interspike interval. Previous authors have speculated on the functional importance of initial doublets. Here we test the hypotheses that these doublets are associated with particular classes of motoneurones or particular physiological conditions. 2. Discharges of inspiratory motoneurones were recorded extracellularly in the thoracic ventral horn of anaesthetized, paralysed cats. Seventy units (35 ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 37 publications
1
21
1
Order By: Relevance
“…The relative threshold for doublet generation (measured as a ratio of current necessary to evoke doublet to the rheobase) exceeded two times rheobase, and there were no statistical differences between groups. It should be mentioned that doublets were observed frequently with increased intensity of current injection, but not in all the cases, which confirms earlier observations (Bawa and Calancie 1983;Kirkwood and Munson 1996;Mr贸wczy艅ski et al 2010). Doublets could be determined in 11 out of 14 slow and 29 out of 35 fast motoneurons in the control group, in 9 out of 12 slow and 27 out of 31 fast motoneurons in the 5wkOL group, and 11 out of 13 slow and 24 out of 29 fast motoneurons in the 12wkOL group.…”
Section: Resultssupporting
confidence: 75%
“…The relative threshold for doublet generation (measured as a ratio of current necessary to evoke doublet to the rheobase) exceeded two times rheobase, and there were no statistical differences between groups. It should be mentioned that doublets were observed frequently with increased intensity of current injection, but not in all the cases, which confirms earlier observations (Bawa and Calancie 1983;Kirkwood and Munson 1996;Mr贸wczy艅ski et al 2010). Doublets could be determined in 11 out of 14 slow and 29 out of 35 fast motoneurons in the control group, in 9 out of 12 slow and 27 out of 31 fast motoneurons in the 5wkOL group, and 11 out of 13 slow and 24 out of 29 fast motoneurons in the 12wkOL group.…”
Section: Resultssupporting
confidence: 75%
“…It has been suggested that doublets occur most often in higher-threshold motor units, but it has also been suggested that any motor unit may be capable of firing doublets (Bawa and Calancie 1983;Garland and Griffin 1999;Kirkwood and Munson 1996). Therefore from the current literature, it is not clear which motor units are more likely to fire doublets.…”
Section: Introductioncontrasting
confidence: 40%
“…Initial doublets, with instantaneous frequencies of 50-300 Hz, are seen in spinal motoneurons during endogenous motor behavior (488,639,673,1417), suggesting that they are not an experimental artifact. Initial doublets may permit motoneurons to generate extra force at the onset of a contraction (476,838), perhaps to overcome inertia, but the phenomenon is not necessarily correlated with a physiological need for strong contractions (639,673).…”
Section: Integration Of Synaptic Input and Firing Modes Of Motoneumentioning
confidence: 99%
“…Initial doublets may permit motoneurons to generate extra force at the onset of a contraction (476,838), perhaps to overcome inertia, but the phenomenon is not necessarily correlated with a physiological need for strong contractions (639,673). An increase in the magnitude and duration of spike AHP contributes to the initial adaptation (48, 62, 1312), dependent on Ca 2+ entry (activating I K Ca ) during the first few spikes (1088,1301).…”
Section: Integration Of Synaptic Input and Firing Modes Of Motoneumentioning
confidence: 99%